A general framework to evaluate economic efficiency with an application to British SME - Jan Průša (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This article formalises the idea of money-metric production frontiers, which we propose as a general framework for nonparametric evaluation of economic efficiency. As we show in our methodological discussion, this improves the flexibility and economic interpretation of our model. The empirical part is the first attempt to test the existence of a size-efficiency relationship among small businesses in the United Kingdom. It is based on a unique panel both with respect to size ranging from agriculture to services and to the ten year time span. We employ statistically robust methods to estimate and analyse sectoral efficiency. Our analysis yields three main insights: (1) Average sectors are expected to be two to four times less efficient than those on the efficient frontier. Great dispersion of efficiency scores highlights the importance of dynamic out-ofequilibrium modelling. (2) There is no evidence of a general economy-wide sizeefficiency relationship. (3) Economic efficiency remained constant over the past ten years.
Keywords: D24; L25; L26; 330; small and medium enterprises; economic efficiency; firm size; robust efficiency estimation; Wirtschaftliche Effizienz; Betriebsgröße; KMU; Theorie; Großbritannien